Enhancing water sustainability index assessment through risk management, IoT, and artificial intelligence in water operation: a review - Septiyana, Diah; Abd Rahman, Mohamed; Mohamed Ariff, Tasnim Firdaus; Sukindar, Nor Aiman; Adesta, Erry Yulian Triblas (Zibeline International Publishing Sdn. Bhd., 2023)
Water is an important element for all living things. It is very important to have sustainability in drinking water operations. This is because sustainability in drinking water operations means continuous water supply without interruption. Sustainability is very related to risk management. This can be said that a good water supply sustainability index must be assessed using good risk management. However existing water sustainability index has proved inaccuracy, this can be seen from the sustainability index parameter that has the same weight between each other. An additional method such as Artificial intelligence and IoT was needed to enhance the accuracy of the water supply sustainability index. This method (artificial intelligence and IoT) was used as an enhancement for risk management parameters based on its severity, thus impacting sustainability index accuracy. In this paper, we propose to review detailed risk management research and operations management for sustainable drinking water supplies. Various challenges (issues) that exist in the water sustainability index that are inside drinking water operations are presented together with the future direction of sustainability index based on artificial intelligence and IoT that can enhance the framework. A good drinking water operation combined with enhanced risk management (IoT and artificial intelligence) can boost the sustainability index (assessment) accuracy.